Are anxiety and fear separable emotions in driving?: laboratory study of behavioural and physiological responses to different driving environments - Barnard, Megan Patricia; Chapman, Peter (Elsevier, 2016)
Research into anxiety and driving has indicated that those higher in anxiety are potentially more dangerous on the roads. However, simulator findings suggest that conclusions are mixed at best. It is possible that anxiety is becoming confused with fear, which has a focus on more clearly defined sources of threat from the environment, as opposed to the internal, thought-related process associated with anxiety. This research aimed to measure feelings of fear, as well as physiological and attentional reactions to increasing levels of accident risk. Trait anxiety was also measured to see if it interacted with levels of risk or its associated reactions. Participants watched videos of driving scenarios with varying levels of accident risk and had to rate how much fear they would feel if they were the driver of the car, whilst skin conductance, heart rate, and eye movements were recorded. Analysis of the data suggested that perceptions of fear increased with increasing levels of accident risk, and skin conductance reflected this pattern. Eye movements, when considered alongside reaction times, indicated different patterns of performance according to different dangerous situations. These effects were independent of trait anxiety, which was only associated with higher rates of disliking driving and use of maladaptive coping mechanisms on questionnaires. It is concluded that these results could provide useful evidence in support for training-based programs; it may also be beneficial to study trait anxiety within a more immersive driving environment and on a larger scale.